(untitled) (Al-Farooq Journal of Sciences, 2026)
In order to avoid downstream scouring and structural failure, efficient energy dissipation is essential to the safe and cost-effective operation of dam spillways. The use of a counter-flow or cross-jet to regulate hydraulic jumps is the main topic of this paper’s analysis of the mechanics and effectiveness of an enhanced reversed flow energy dissipation technique. Reversed flow techniques greatly reduce the necessary stilling basin length by generating a forced hydraulic jump, which lowers construction costs and improves structural safety. This study summarizes analytical and experimental results from important studies, showing that these techniques can significantly shorten stilling basin length and hydraulic jump length. The results demonstrate the potential of reversed flow dissipators as a reliable and effective substitute for traditional energy dissipators, especially in high-velocity flow situations where abrasion and cavitation present serious risks.